Analisis Faktor Risiko Indeks Massa Tubuh, Riwayat Hipertensi, dan Riwayat Preeklampsia terhadap Kejadian Preeklampsia pada Ibu Hamil - Tia Tahnia; Defrin Defrin; Firdawati Firdawati; Rima Semiarty; Roza Sriyanti; Lusiana El Sinta Bustami (Universitas Muhamadiyah Manado, 2026)
Preeclampsia is a pregnancy complication that significantly contributes to maternal and neonatal morbidity and mortality worldwide. Globally, it affects approximately 3–8% of pregnancies and causes more than 70,000 maternal deaths each year. In Indonesia, preeclampsia accounts for around 30% of the 4,151 maternal deaths reported in 2024. In Padang City, there were 254 cases in 2023 and 129 cases in 2024, with Puskesmas Bungus having the highest prevalence (7.2% and 3.77%). This study aimed to analyze the association between body mass index (BMI), history of hypertension, and history of preeclampsia with the incidence of preeclampsia among pregnant women at Puskesmas Bungus, Padang. This study used a quantitative case-control design involving 50 cases and 50 controls. Data were analyzed using chi-square and logistic regression tests. The results showed significant associations between obesity (p=0.031; OR=2.897), history of preeclampsia (p=0.006; OR=13.821), and history of hypertension (p=0.002; OR=17.216) with the incidence of preeclampsia. Multivariate analysis identified history of hypertension as the most dominant factor associated with preeclampsia. This study concludes that obesity, history of hypertension, and history of preeclampsia are significant risk factors for preeclampsia among pregnant women. Strengthening early detection and routine antenatal care for high-risk pregnancies is necessary to reduce maternal complications associated with preeclampsia.